The Givenness without Phenomena of Jean-Luc Marion: A Hermeneutic-Phenomenological Critic - Cazzanelli, Stefano (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The aim of the present article is to analyze the phenomenology of givenness of Jean-Luc Marion and to outline some phenomenological and hermeneutical critics. In the first place we want to show how the interpretations that the French thinker describes about the givenness in the «first Heidegger» are clearly influenced by the philosophy of the so-called «second Heidegger». Therefore, they do not take into account the hermeneutical background that inspires every analysis of Heidegger during the 20s. Secondly, we will bring to light how a phenomenology of givenness that redirects every appearance to the pure giving of phenomena is more suitable for a theoretical-metaphysical issue than for a real phenomenological or hermeneutical approach.